(untitled) (Mathematical Proceedings of The Widya Mandira Catholic University, 2025)
This study employs a Systematic Literature Review (SLR) to investigate the integration of Problem-Solving approaches within STEM (Science, Technology, Engineering, and Mathematics) education and its effectiveness in enhancing students’ critical thinking skills. Literature was systematically collected from reputable databases, namely Google Scholar, DOAJ, and Scopus, with publications ranging from 2015 to 2025 as the inclusion criteria. The findings reveal that integrating Problem-Solving into STEM learning significantly contributes to the development of critical thinking by engaging students in authentic problems, project-based learning, and inquiry-oriented activities. These strategies encourage learners to evaluate information critically, formulate solutions, and make evidence-based decisions. Moreover, teachers play an essential role as active facilitators, while the integration of digital technologies further strengthens learning outcomes. However, several challenges persist in its implementation, including limited teacher competence in designing interdisciplinary learning, inadequate facilities and resources, and varying levels of student readiness across educational settings. The review highlights both the potential and the barriers of implementing Problem-Solving in STEM, providing valuable insights for policymakers, educators, and researchers to design more effective and sustainable educational practices that foster 21st-century skills. Future research is recommended to address long-term impacts, inclusive practices in resource-limited contexts, and teacher professional development to maximize the benefits of this approach